Separation and identification of indene–C70 bisadduct isomers - Zhang, Bolong; Subbiah, Jegadesan; Jones, David J.; Wong, Wallace Wing Ho (Beilstein Journal of Organic Chemistry, 2016)
Following an initial work on the isolation of a single geometric isomer from an indene–C70 bisadduct (IC70BA) mixture, we report the full fractionation and identification of the bisadduct species in the material. Eleven fractions of IC70BA isomers were separated by high-performance liquid chromatography. A number of fractions contained relatively pure isomer species and their configuration were deduced using a variety of analytical techniques including 1H and 13C NMR and UV–vis spectroscopy. The electrochemical properties and the organic solar cell device performance were investigated for fractions where a reasonable quantity of sample could be isolated.
Keywords: chromatographic separation; electron acceptor; fullerene bisadduct; organic solar cell; regioisomers